Moxifloxacin Monotherapy in Left-Sided Staphylococcus aureus Endocarditis - Yucel Colkesen (Case Reports in Infectious Diseases)
Staphylococcus aureus is the major cause of endocarditis, and its mortality has remained high despite therapeutic procedures over time. A case of left-sided native valve endocarditis caused by methicillin-sensitive Staphylococcus aureus which responded well to moxifloxacin monotherapy is described. An 83-year-old woman with a history of current hospitalization presented with fatigue and fever. Transthoracic echocardiography depicted vegetation, and blood cultures were positive for Staphylococcus aureus. After a 14-day intravenous administration of moxifloxacin, a good clinical response was achieved, and antibiotic regimen transitioned to oral moxifloxacin for an additional four-week therapy.